The Influence of Green Leadership, Teacher Work Culture and Work Motivation on the Performance of Elementary School Teachers - Mega Herniyanti; Metroyadi Metroyadi; Sutarto Hadi (Universitas Negeri Malang, 2025)
Abstract: This study aims to describe green leadership, teacher work culture, work motivation, and teacher performance, as well as analyze the direct and indirect effects of these variables on the performance of public elementary school teachers in Salam Babaris District, Tapin Regency. The study employed a quantitative approach with a descriptive method. The population consisted of 97 teachers, all of whom were selected as research samples. Data were collected using questionnaires that met the validity and reliability criteria. Data analysis was conducted using descriptive statistics and path analysis. The findings reveal that green leadership, teacher work culture, and work motivation fall into the good category. Statistically, green leadership, teacher work culture, and work motivation have direct effects on teacher performance. Additionally, work motivation functions as a mediating variable that strengthens the indirect effects of green leadership and teacher work culture on teacher performance. These results indicate that visionary and inspirational school leadership, a positive and supportive work culture, and high work motivation contribute to improving teacher performance. The study recommends that school principals enhance environmentally oriented leadership, provide clearer explanations of task responsibilities, and promote open and fair communication to create a supportive working environment for sustainable improvement in teacher performance. Keywords: Green Leadership; Teacher Work Culture; Work Motivation; Teacher Performance